2007
DOI: 10.1002/bbb.31
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane ethanol production in Brazil: an expansion model sensitive to socioeconomic and environmental concerns

Abstract: Brazilian agriculture is characteristically dynamic; land and production resources have a skewed ownership distribution; and agricultural production is essential for small holders of rural poor regions. Also, the main agricultural land use is composed of pastures where extensive livestock production prevails. Because of increasing demand Brazil is expected to expand its sugarcane-based ethanol production. Addressing concerns about social and environmental impacts of such an expansion requires careful considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 7 publications
1
29
0
4
Order By: Relevance
“…WALTER et al (2011) stated that Brazil will continue to be a major producer of ethanol in the global market in the coming years. Ethanol production site conditions are relatively favorable, taking into account factors such as the availability of land and climate, the long-term experience, existing technology and the size of the domestic market.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…WALTER et al (2011) stated that Brazil will continue to be a major producer of ethanol in the global market in the coming years. Ethanol production site conditions are relatively favorable, taking into account factors such as the availability of land and climate, the long-term experience, existing technology and the size of the domestic market.…”
Section: Introductionmentioning
confidence: 99%
“…Goiás participates with 8.52% of the entire area for the cultivation of sugarcane in Brazil (CONAB, 2012). SPAROVEK et al (2007), GOLDEMBERG et al (2008), MARTHA JR. (2008) indicated that the expansion of sugarcane has developed or will push over pasture areas in the Center-South region. In Goiás, there was alternative crops in 75,058 hectares in 2009/10, 61% of the areas were previously occupied by pasture, 36% were intended for soybean cultivation and 3% for corn, which were incorporated into the sugarcane production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abramovay ( Um modelo de expansão da cana-de-açúcar para o Brasil deve se basear em uma avaliação multicriterial, e considerar a complexa realidade das diferentes regiões para potencial expansão, incluindo proteção à segurança alimentar, aos pequenos produtores e à proteção da biodiversidade -como apresentado no modelo proposto por Sparovek et al (2007).…”
Section: Pressão Sobre Pequenas Propriedadesunclassified
“…No caso do etanol, como exemplo de meta de proteção à agricultura familiar e à biodiversidade, uma meta poderia definir o aumento da participação de culturas integradas no fornecimento de agroenergias (LOMBARDI et al, 2009;SPAROVEK et al, 2007).…”
Section: Definição Do Escopo E Diagnósticounclassified